A Preliminary Examination of Teachers’ and Students’ Perspectives on Autonomy-Supportive Instructional Behaviors - Betsy Ng; Woon Chia Liu; C. K. John Wang (Qualitative Research in Education, 2015)
The present study focuses on the perspectives of teachers and students in Singapore schools after an autonomy-supportive classroom intervention. Nurturing of students to become motivated and self-regulated learners can be achieved by promoting an autonomy-supportive learning climate. This study examines the perspectives of teachers and students in an in-depth and meaningful manner after the classroom intervention. Through students’ viewpoints, teachers can understand their structure of teaching style and students’ expectations. Findings of semi-structured interviews with students and teachers were analyzed, with emerging themes discussed in the context of literature. Based on qualitative data, this preliminary study explores a rich and meaningful insight to students’ expectations of their teachers and teachers’ expectations towards their students. The qualitative data provided relevant and practical insights into the classroom intervention, suggesting that teachers should be aware of their instructional behaviors in class as such acts might have ramification on students’ perception, motivation and learning. Limitations and implications are also discussed.